DUST STORM AND ATMOSPHERE AIR POLLUTION IN UZBEKISTAN - Feruza I. Salomova; Nigora O. Ahmadalieva; Khosiyat A. Sadullaeva; Guzal F. Sherkuzieva; Nargiza F. Yarmukhamedova; Bakhritdin Q. Nurmatov (Central Asian Journal of Medicine, 2022)
Aim of the study: a hygienic assessment of the state of atmospheric air according to the Center for Hydrometeorological Service of the Republic of Uzbekistan and hygienic assessment of dust concentrations in the air based on laboratory control. Materials and methods: The Center of the Hydrometeorological Service of the Republic of Uzbekistan monitors air pollution in the cities of the Republic. The monitoring program covers 5 main pollutants: dust (suspended solids), carbon monoxide (carbon monoxide), nitrogen dioxide, sulfur dioxide, nitric oxide. The information obtained from 63 stationary observation posts allows us to judge the average level of air pollution in the republic as a whole and to calculate the atmospheric pollution index, which gives an integral characteristic of the level of air pollution for the city over the year. Conclusions: An analysis of the data shows that over the studied period, an increased degree of atmospheric pollution index was observed only in Angren: 2014 - 5.12, 2016 - 5.32, 2017 - 5.30. In other cities of the republic, elevated API was not observed. It can be assumed that these indicators were achieved as a result of measures to reduce harmful atmospheric emissions through the construction and reconstruction of capture systems and dust and gas cleaning of individual workshops and industries, as well as work on the transfer of motor vehicles to alternative fuels. Dust storm observed on November 4, 2021 in the cities of the Republic of Uzbekistan polluted the atmosphere. On November 5, the amount of dust in the air was found to be 50 times the allowable concentration. On November 21, the amount of dust in the air decreased to the allowable concentration.